POTENTIAL YIELD OF DEEP SEA SHRIMP RESOURCES IN THE SOUTHERN JAVA OF THE INDIAN OCEAN EEZ WATERS - Ali Suman; Muhammad Rijal; Gatut Bintoro (Research Center for Fisheries, 2008)
Study on the potential yield of deep sea shrimp in the south off Java waters (lndian Ocean) was carried out based on data collected from the survey conducted between May and June 2005 using Baruna Jaya IV research vessel. This study was basically conducted by applying swept area method.